Induction of Granulysin and Perforin Cytolytic Mediator Expression in 10-Week-Old Infants Vaccinated with BCG at Birth - Patricia L. Semple; Marcia Watkins; Virginia Davids; Alan M. Krensky; Willem A. Hanekom; Gilla Kaplan; Stanley Ress (Clinical and Developmental Immunology)
Background. While vaccination at birth with Mycobacterium bovis Bacilli Calmette-Guérin (BCG) protects against severe childhood tuberculosis, there is no consensus as to which components of the BCG-induced immune response mediate this protection. However, granulysin and perforin, found in the granules of cytotoxic T lymphocytes and Natural Killer (NK) cells, can kill intracellular mycobacteria and are implicated in protection against Mycobacterium tuberculosis. Methods. We compared the cellular expression of granulysin and perforin cytolytic molecules in cord blood and peripheral blood from 10-week-old infants vaccinated at birth with either Japanese or Danish BCG, administered either intradermally or percutaneously. Results. In cord blood, only CD56+ NK cells expressed granulysin and perforin constitutively. These cytolytic mediators were upregulated in CD4+ and CD8+ cord blood cells by ex vivo stimulation with BCG but not with PPD. Following BCG vaccination of neonates, both BCG and PPD induced increased expression of granulysin and perforin by CD4+ and CD8+ T cells. There was no difference in expression of cytolytic molecules according to vaccination route or strain. Conclusions. Constitutive expression of perforin and granulysin by cord blood NK-cells likely provides innate immunity, while BCG vaccination-induced expression of these cytolytic mediators may contribute towards protection of the neonate against tuberculosis.